2020
DOI: 10.3390/biom10040643
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Interferon β-Cisplatin Treatment Enhances the Surface Exposure of Calreticulin in Cancer Cells via an Interferon Regulatory Factor 1-Dependent Manner

Abstract: Immunogenic cell death (ICD) refers to a unique form of cell death that activates an adaptive immune response against dead-cell-associated antigens. Accumulating evidence indicates that the efficacy of conventional anticancer agents relies on not only their direct cytostatic/cytotoxic effects but also the activation of antitumor ICD. Common anticancer ICD inducers include certain chemotherapeutic agents (such as anthracyclines, oxaliplatin, and bortezomib), radiotherapy, photodynamic therapy (PDT), and oncolyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 58 publications
0
12
0
Order By: Relevance
“…Also, IFN plays a crucial role in tumor immunity. On the one hand, IFN exerts an anti-tumour effect, suppresses tumour proliferation, and perform immune elimination by activating cytotoxic lymphocytes (CTLs), dendritic cells (DCS) and other immune cells [ 88 ]; On the other hand, IFN-γ upregulates PD-L1 and cause programmed death of immune cells, which enables tumour cells to escape the destructive effect of the immune system, resulting in anti-tumour treatment tolerance [ 89 ]. Therefore, it is necessary to ensure that patients can benefit from immunotherapy while assuring the stable antitumor effect of IFN.…”
Section: Discussionmentioning
confidence: 99%
“…Also, IFN plays a crucial role in tumor immunity. On the one hand, IFN exerts an anti-tumour effect, suppresses tumour proliferation, and perform immune elimination by activating cytotoxic lymphocytes (CTLs), dendritic cells (DCS) and other immune cells [ 88 ]; On the other hand, IFN-γ upregulates PD-L1 and cause programmed death of immune cells, which enables tumour cells to escape the destructive effect of the immune system, resulting in anti-tumour treatment tolerance [ 89 ]. Therefore, it is necessary to ensure that patients can benefit from immunotherapy while assuring the stable antitumor effect of IFN.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another report showed that free oxaliplatin or phase-transition nanoparticles loaded with oxaliplatin caused translocation of CRT to the surface of ID8 mouse ovarian surface epithelial cell line, which is used as a syngeneic mouse model for human ovarian cancer. Moreover, studies demonstrated that the inhibition of ROS production in ID8 cells completely blocked appearance of surface CRT, pointing at ROS requirement in oxaliplatin-mediated chaperone expression [ 111 ].…”
Section: The Role Of Calreticulin In Epithelial Ovarian Cancermentioning
confidence: 99%
“…However, in nearly one-third of patients, cancerous growth has already spread to regional lymph nodes at the time of diagnosis [67]. Therefore, it is necessary to investigate novel prognostic techniques for early-stage detection, which employ new biomarkers in a vital role [68][69][70][71][72][73]. Furthermore, characterizing the immune system, profiling the TME, and constructing BRCA immunotherapies are also known as critical keys in cancer research [74,75].…”
Section: Discussionmentioning
confidence: 99%